2020
DOI: 10.3390/jcm9030827
|View full text |Cite
|
Sign up to set email alerts
|

Improved Isolation and Culture of Urine-Derived Stem Cells (USCs) and Enhanced Production of Immune Cells from the USC-Derived Induced Pluripotent Stem Cells

Abstract: The availability of autologous adult stem cells is one of the essential prerequisites for human stem cell therapy. Urine-derived stem cells (USCs) are considered as desirable cell sources for cell therapy because donor-specific USCs are easily and non-invasively obtained from urine. Efficient isolation, expansion, and differentiation methods of USCs are necessary to increase their availability. Here, we developed a method for efficient isolation and expansion of USCs using Matrigel, and the rho-associated prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 84 publications
(115 reference statements)
1
18
1
Order By: Relevance
“…The tissues were chopped and the cells from the tissues were cultured in α-MEM supplemented with 10% FBS and 1% PS. The isolation and characterization of AD-MSCs and USCs were carried out as described in our recent publication [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…The tissues were chopped and the cells from the tissues were cultured in α-MEM supplemented with 10% FBS and 1% PS. The isolation and characterization of AD-MSCs and USCs were carried out as described in our recent publication [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“… Joo et al (2012) made a similar observation during the differentiation and proliferation of endothelial cells derived from an embryonic stem cell (ESC)-derived Flk1+ mesodermal precursor cells. Recently, Kim et al (2020) found that ROCK inhibitor Y-27632 together with Matrigel improved the isolation, proliferation rate, and differentiation potential of urine-derived stem cells in humans. Furthermore, ROCK inhibitors have been used to promote proliferation, viability, and differentiation of mesenchymal stem cells ( Baharvand et al, 2010 ; Mellott et al, 2014 ; Nakamura et al, 2014 ; Li et al, 2015 ).…”
Section: Roles Of Rock In Embryonic Tissue Segregation and Stem Cell mentioning
confidence: 99%
“…However, whether USCs cultured by this method remain the same or whether the differences between USCs cultured by different methods lead to different therapeutic outcomes is still unknown. Another solution that faces the same dilemma is reconstituting the culture conditions of the USCs by adding certain nutritional supplements, seeding the USCs on other extracellular matrix components, and taking oxygen tension into account to improve the isolation and proliferation of the USCs [ 67 , 113 ]. Considering batch-to-batch variation, the quality control of the USCs is of great significance.…”
Section: Reviewmentioning
confidence: 99%